Stomach Content Analysis of Pangasius polyuranodon Captured In The Siak River, Tualang Village, Siak Regency, Riau Province - Nurlaili '; Windarti '; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Pangasius polyuranodon is one of freshwater fishes that inhabit the Siak River in Riau. This fish has a high economical value and it is a main ingredient for many Riau’s traditional food. However, information on biological aspects of this fish is limited. To understand the stomach content analysis of this fish, a study has been conducted from January – March 2015. The fish was sampled in the Siak River using of the gill net. Stomach content of the fish was analyzed as a basis to calculate the Preponderance Index (PI). There were 118 fishes captured, but 33 of them had empty stomach and they cannot be used for stomach content analysis. Results shown that the main food of P. polyuranodon was a benthic animal such as gastropods (PI 43.91%), bivalve (PI 17.77%), cricket (PI 5.39%), fish (PI 1.52%), crustacean (PI 1.26%), bones (PI 0.24%) and Elais guinensis (PI 28.49%), leaves (PI 1.19%) and Archidendron (0.05%). Empty shells of gastropods and bivalve and Elaeis kernels were found in the intestine of the fish, indicates that the fish dispose these hard materials through their feces. Based on data obtained, it can be concluded that the main food of P. polyuranodon is benthic animals such as gastropod and bivalve and this fish can be categorized as omnivore leads to carnivore.Keyword: Pangasius polyuranodon, Stomach Content Analysis, Index of Preponderance